Pengembangan Student Worksheet Model MORE Berbasis Teori Konstruktivistik Sosial Vygotsky di MAN 1 Pontianak - Sutoyo Budiharto; Ismet Basuki (Pedagogi: Jurnal Ilmu Pendidikan, 2021)
This study aims to develop student worksheets of good quality and effectiveness to improve students' knowledge competencies. The student worksheet developed refers to the MORE (Model-Observe-Reflect-Explain) learning model based on Vygotsky's social constructivist theory. This development research refers to the steps developed by Thiagarajan, namely the 4-D model. Data collection techniques in this study applied interviews, observation, and tests. The analysis technique used is descriptive quantitative. The empirical test of increasing knowledge competence uses the pre-experimental method with one group pretest-posttest design. Data on knowledge competency improvement were analyzed using the paired sample t-test. The subjects of this study were students of class X IPS 1 at Moslem Senior High School (MAN). The results of this study are as follows: first, the MORE student worksheet model based on Vygotsky's social constructivist theory has a very good quality. Second, the MORE student worksheet model based on Vygotsky's social constructivist theory is effective for history learning.